Availability Based Maintenance Analysis for System With Repair Time Threshold - Kontrec, Nataša; Panić, Stefan; Panić, Biljana (Yugoslav Journal of Operations Research; Vol 35 No 3 (2025)DO - 10.2298/YJOR240315003K, 2025)
In this paper, we are observing a reparable system comprised of several components. The aim is to determine at which repair rate the system achieves the highest availability. To accomplish that, the procedure for the calculation of the repair rate in function of the desired level of availability for the system with a predetermined repair rate threshold is created. The presented approach is based on the exploration of the probability density function (PDF) of a system's repair time by observing the probability that repair rates of its components surpass a determined threshold. The obtained results can be applied in reliability theory, maintenance planning, and many other fields. To prove the application of the developed model, the results are verified by a numerical example for an unmanned vehicle system.